Team experiences of the root cause analysis process after a sentinel event: a qualitative case study - Silje Liepelt; Hildegunn Sundal; Ralf Kirchhoff (BMC, 2023)
Abstract Background Root cause analysis (RCA) is a systematic approach, typically involving several stages, used in healthcare to identify the underlying causes of a medical error or sentinel event. This study focuses on how members of a Norwegian RCA team experience aspects of an RCA process and whether it complies with the Norwegian RCA method. Method Based on a sentinel event in which a child died unexpectedly during childbirth in a Norwegian hospital in 2021, the following research questions are addressed: 1. What was the RCA team's experience of the RCA process? 2. Was there compliance with the Norwegian RCA method in this case? A case study was chosen out of the desire to understand complex social phenomena and to allow in-depth focus on a case. Results The result covered three main themes. The first theme related to the hospital's management system and aspects of the case that made it challenging to follow all recommendations in the Norwegian RCA guidelines. The second theme encompassed external and internal assessment. The RCA team was composed of members with methodological and medical expertise. However, the police's involvement in the case made it complex for the team to carry out the process. The third and final theme covered intrapersonal challenges RCA team members faced. Team members experienced various challenges during the RCA process, including being neutral, dealing with role-related challenges, grappling with ambivalence, and managing the additional time burden and resource constraints. As anticipated in the RCA guidelines, the team's ability to remain neutral was tested. Conclusion The findings of this study can help stakeholders better comprehend how an inter-professional RCA teamwork intervention can affect a healthcare organization and enhance the teamwork experience of healthcare staff while facilitating improvements in work processes and patient safety. Additionally, these results can guide stakeholders in creating, executing, utilizing, and educating others about RCA processes.